Dashboard monitoring kelengkapan rekam medis elektronik berbasis SIMRS - Wiwid Kurniati; Edy Susena (Holistik Jurnal Kesehatan, 2026)
Background: Completeness of Electronic Medical Records (EMRs) is an important indicator of the quality of clinical documentation and healthcare services. However, monitoring the completeness of EMRs in hospitals remains suboptimal because it is still conducted manually. Therefore, a monitoring dashboard integrated with the Hospital Management Information System (HMIS) is required to facilitate accurate and real-time monitoring of clinical documentation. Purpose: To develop an HMIS-based dashboard for monitoring the completeness of Electronic Medical Records and to evaluate its implementation in improving the quality of clinical documentation in the inpatient ward. Method: A Research and Development (R&D) method with a pretest-posttest design. This research was conducted in April-May 2026 in the Camar Inpatient Ward, Ajibarang Regional Hospital. The samples consisted of 132 EMR documents assessed before the dashboard implementation and 126 EMR documents assessed after the implementation. The research stages included identifying the initial conditions, developing the dashboard, implementing the system, and evaluating the completeness of clinical documentation. Data were analyzed descriptively by comparing the percentages of EMR completeness before and after the dashboard implementation. Results: The average completeness rate of EMRs before the dashboard implementation was 32.4%, indicating that several clinical documentation components remained incomplete. Following the implementation of the HMIS-based monitoring dashboard, all assessed documentation components reached 100% completeness. The dashboard provided real-time monitoring of documentation completeness, summaries of incomplete records, and a warning system for incomplete clinical documentation. Conclusion: The HMIS-based Electronic Medical Record completeness monitoring dashboard was effective in improving the quality of clinical documentation and supporting faster, more structured, and more efficient monitoring and evaluation processes. Suggestion: Hospitals are encouraged to maintain and expand the implementation of the monitoring dashboard across other inpatient wards to ensure consistent and sustainable completeness of Electronic Medical Records.   Keywords: Clinical Documentation Quality; Electronic Medical Records; Hospital Management Information System; Monitoring Dashboard.